Case Study of Nursing Care in Patients with Pulmonary Tuberculosis at St. Anthony's Hospital (Nursing Care Journal, 2022)
The World Health Organization (WHO) declares pulmonary TB as a very important and serious public health problem worldwide and is a disease that causes a global emergency because in some countries of the world, pulmonary TB disease is uncontrolled due to the large number of patients who are not successfully cured, as well as as the main cause of death caused by infectious diseases. the number of patients with pulmonary TB by 0.36% in West Kalimantan. According to the Pontianak City Health Profile in 2017, it was found that lung TB sufferers in 2016 in pontianak city as much as 64.28%, while in 2017 as much as 77.19%, based on this figure can be known to increase the percentage of pulmonary TB in 2017 compared to 2016. This study aims to find out the picture of nursing care in patients with respiratory system disorders, Pulmonary Tuberculosis (pulmonary TB). The research method used is the case study method. A case study is a study that explores a nursing problem in detail, has in-depth data retrieval and includes a variety of sources of information. The results of the study: after a study obtained the results that psien before illness is an active smoker, this is supported by Novita statement, smoking behavior can cause an increased risk of tb to 2 times. Problems are found ineffectiveness of breath patterns, activity intolerance, readiness to improve sleep.